Written Monument "al-Qawanin" in the Mamluk-Kipchak language: textological analysis (Journal of Oriental Studies, 2016)
The article considers the textological analysis of written monument al-Kavanin" written in the Mamluk-Kipchak language during the authority of Mamluks
Keywords: "Al-Qawanin"; the Turkic-kipchak language; written monuments; grammar books; textological analysis.